Inventarization of Pteridophytes Plants Species in Sriwijaya University Campus Area, Indralaya, South Sumatera - Aminasih, Nita; Marisa, Hanifa; Harmida, Harmida (Proceeding International Conference on Global Resource Conservation, 2013)
A taxonomic survey had been done for inventarization of Pteridophytes plants species at The University of Sriwijaya campus area, at April 2011. It was found 30 species that categorized in 11 family, where 24 of those species are herb life-form and 6 of them were bush fern; 27 species were life as terrestrial plants and 3 of them were swampy fern. Gleichenia linearis is the common species found as terrestrial fern, Davalia denticulate common for epiphyte, and Salvinia natans was often found as hydrophytes.Keywords: pteridophytes, species, family, terrestrial, swampy, epiphytes, hydrophytes